Cost of Educational Deprivation: A Case of Pakistan - Rafique, Nayar; Khawaja, Idrees (International Journal of Economics and Financial Issues, 2020)
Being a developing country, with a hugely deprived educational profile, Pakistan is facing huge cost of its millions of uneducated and out of school population. Though we know that lack of education imposes costs on individuals and society, however no precise estimates of such costs are available. This research attempted to explain the cost associated with massive educationally deprived population in Pakistan by using HIES-PSLM 2018-19 dataset in the light of human capital theory and capability approach. The results showed gigantic loss of income for Pakistan due to the current educational profile of labor force which includes enormous population with no education or lower level of education. Given the results, we can say that if every individual in Pakistan receives at least ten year of schooling according to SDG Goal 4, then Pakistan could have thousands of billion more income which not only stimulate further economic growth but a wider development in every sphere of life at individual as well as collective level. Keywords: Pakistan, Development, Human Capital, Returns to Education, Cost, SDGs JEL Classifications: O1, O2, I2, I3 DOI: https://doi.org/10.32479/ijefi.10335